Rozum wobec żałoby: argumenty apologetyczne C.S. Lewisa w obliczu dotkliwej straty. Część I: Rozum (Przegląd Religioznawczy – The Religious Studies Review, 2020)
Clive S. Lewis is thought to be one of the most important contemporary Christian apologist. In his works, Lewis argued against naturalism and put forward arguments in support of theism. In doing so, he referred to experience and made use of laws of logic and probabilistic reasoning, hence meeting rationality criteria. Part I discusses Lewis’s arguments from the existence of morality, reason, desires and numinous experiences. It presents a basal criticism of these arguments. Except of the ptresentation of those arguments and their analysis the aim of the paper is to provide a basis for a comparison (in Part II) of the anti-naturalistic arguments with what Lewis wrote about God, faith and life after death in the period following the passing of his wife, a great loss for the thinker.